Evaluating the Distance Learning Experience Provided to Students with Special Needs in Saudi Arabia from the Teacher’s Viewpoints - Aldoseri, Fatimah Hamad; Almuhanna, Manal Abdulrahman (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to evaluate the experience of distance learning provided to students with special needs in general education from the teachers’ perspective in KSA, by identifying the level of readiness of distance learning provided to students with special needs, its advantages, obstacles, and suggestions for improvement. A descriptive survey method was used to achieve the study objectives, and a sample consisting of (111) female special education teachers in Riyadh city was given a questionnaire. The results showed that the level of readiness for distance learning provided to students with special needs and its advantages obtained a total average of (3.21 out of 5); That is, to a moderate degree in both. The results also indicated the presence of obstacles to a high degree, which obtained a total average of (3.68 out of 5). The results revealed the need for enhancing families’ role and providing appropriate evaluation tools. Based on the results, the study presented a number of recommendations, including the need to design interactive educational materials that suit students with special needs and take into account their individual differences, and choose appropriate strategies for education them remotely.